Novel methods for the isolation and purification of exoglycosidases - Pannifer, Susan (Division of Medical Biochemistry and Structural Biology, 2017)
A number of exoglycosidases have been prepared from bacterial and plant sources using established methods for the separation of enzymes, in conjunction with certain novel purification systems hitherto not described in the literature for these enzymes. The enzyme, beta-galactosidase from E. coli has been prepared using previously described methods of phase separation and ion-exchange chromatography. As a final step in this purification, the use of a new hydroxyl-rich chromatographic support for the isolation of high-grade enzyme suitable for use in enzyme immunoassays was investigated. Methods have also been studied for the recovery of alpha-mannosidase as a by-product of the procedure used for the extraction of urease from jack bean (Canavalia ensiformis). The inclusion of a novel step involving the use of hydrophobic-interaction chromatography on Phenyl-Sepharose led to excellent recoveries of enzyme suitable for commercial use. Studies on a second glycosidase, beta-N-acetylhexosaminidase, from the same source (jack bean) paved the way for an adaptation of existing purification methods to provide increased yields and an improved quality of enzyme. Since the research unit in which this work was performed is associated with commercial organizations responsible for the preparation and marketing of biologically active products, it is important that the methods of purification described in this thesis are compatible with the requirements for largescale purification.